2018
DOI: 10.3310/eme05070
|View full text |Cite
|
Sign up to set email alerts
|

Radically open dialectical behaviour therapy for refractory depression: the RefraMED RCT

Abstract: Background About one-third of patients who are depressed do not respond to antidepressant medication (ADM) and traditional psychotherapy shows limited benefits. However, most randomised trials have excluded the most sick patients, especially with comorbid personality disorder. Radically open dialectical behaviour therapy (RO DBT) is a new treatment targeting emotionally overcontrolled personality, which is common in refractory depression. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 138 publications
2
20
0
Order By: Relevance
“…Preliminary research also suggests that techniques in radically open dialectical behaviour therapy (RO DBT) such as social signalling, trust signalling and interpersonal effectiveness can enhance social connectedness. [53][54][55] Low detachment Although, in general, low detachment may be a socially desirable interpersonal quality, individuals maladaptively low in detachment tend to be interpersonally intense and have lower quality or shallow relationships. Such intense interpersonal styles may be found in histrionic and dependent PD, BPD and narcissistic exhibitionism, and excessive excitement seeking might be seen in Stephanie N. Mullins-Sweatt et al 1 Communication analysis 1 Interpersonal effectiveness [2][3][4] Complementarity 1 Social signalling [2][3][4] Interpersonal group therapy 1 Trust signalling [2][3][4] Low detachment Behavioural experiments 5 Cognitive restructuring 5 Interpersonal group therapy 6…”
Section: Treatment Of Personalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary research also suggests that techniques in radically open dialectical behaviour therapy (RO DBT) such as social signalling, trust signalling and interpersonal effectiveness can enhance social connectedness. [53][54][55] Low detachment Although, in general, low detachment may be a socially desirable interpersonal quality, individuals maladaptively low in detachment tend to be interpersonally intense and have lower quality or shallow relationships. Such intense interpersonal styles may be found in histrionic and dependent PD, BPD and narcissistic exhibitionism, and excessive excitement seeking might be seen in Stephanie N. Mullins-Sweatt et al 1 Communication analysis 1 Interpersonal effectiveness [2][3][4] Complementarity 1 Social signalling [2][3][4] Interpersonal group therapy 1 Trust signalling [2][3][4] Low detachment Behavioural experiments 5 Cognitive restructuring 5 Interpersonal group therapy 6…”
Section: Treatment Of Personalitymentioning
confidence: 99%
“…While five clinical trials have been conducted on RO DBT, including evidence of preliminary support for anorexia nervosa 54 and a randomized control trial for treatment-resistant depression, 53 the largest and most recent randomized control trial found no significant differences between RO DBT and treatment-as-usual groups. 55 However, evidence supporting change in theorized mechanisms of the treatment (psychological flexibility and emotional coping) were found. 55 Given the rigidity and socially reinforcing elements characteristic of low disinhibition, a transdiagnostic treatment may ultimately be most efficacious.…”
Section: Low Disinhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants received TAU, including prescribed antidepressant medication or psychotherapy. 13 Participants in the control group could also access any treatment from the NHS or privately, except standard DBT. At each follow-up assessors asked participants to report their antidepressant medication and adherence to it, and psychotherapy accessed since their previous assessment or in the 6 months before their baseline assessment.…”
Section: Taumentioning
confidence: 99%
“…10,11 This trial aimed to assess the efficacy of RO DBT for refractory depression, 12 and whether RO DBT causes identifiable harms. 13…”
mentioning
confidence: 99%